A mixed integer linear programming model for minimum backbone grid - Mei, Wenwen; Sun, Zhiyuan; He, Yuanjian; Liu, Mosi; Gong, Xianfu; Li, Peijie (Frontiers in Energy Research, 2023)
The power system was damaged by extreme weather more and more frequently in the past few years. To improve the power system’s resilience, a mixed integer linear programming (MILP) model with network connectivity constraints for a minimum backbone grid is proposed. In the model, some constraints are presented to consider the practical application requirements. Especially, to avoid islands in the minimum backbone grid, a set of linear constraints based on single-commodity flow formulations is proposed to ensure connectivity of the backbone grid. The simulations on the IEEE-39 bus system and the French 1888 bus system verify the validity of the proposed model. They further show that the proposed model can be solved with high computational efficiency.